2006
DOI: 10.1182/blood-2006-03-009449
|View full text |Cite
|
Sign up to set email alerts
|

Impaired megakaryocytopoiesis in type 2B von Willebrand disease with severe thrombocytopenia

Abstract: In type 2B von Willebrand disease, there is spontaneous binding of mutated von Willebrand factor (VWF) multimers to platelets. Here we report a family in which severe thrombocytopenia may also be linked to abnormal megakaryocytopoiesis. A heterozygous mutation in the VWF A1 domain gave a R1308P substitution in an interactive site for glycoprotein Ib␣ (GPIb␣). Electron microscopy showed clusters of platelets in close contact. Binding of antibodies to the GPIb␣ N-terminal domain was decreased, whereas GPIX and G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
78
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(84 citation statements)
references
References 53 publications
4
78
2
Order By: Relevance
“…It has been previously reported that VWF exists on the surface of cultured megakaryocytes in a 2B-VWD patient. 24 Unlike the findings with this 2B-VWD patient, we observed a VWF distribution in megakaryocytes of hTg G233V animals that is granular and intracellular with no detectable surface VWF antigen. This still does not address whether the VWF adhering to the surface of hTg G233V platelets is a consequence of platelet release or plasmaderived.…”
contrasting
confidence: 55%
“…It has been previously reported that VWF exists on the surface of cultured megakaryocytes in a 2B-VWD patient. 24 Unlike the findings with this 2B-VWD patient, we observed a VWF distribution in megakaryocytes of hTg G233V animals that is granular and intracellular with no detectable surface VWF antigen. This still does not address whether the VWF adhering to the surface of hTg G233V platelets is a consequence of platelet release or plasmaderived.…”
contrasting
confidence: 55%
“…Indeed, it has been recently reported that type 2B vWF impairs human bone marrow megakaryocytopoiesis as determined by ultrastructural changes in bone marrow megakaryocytes. 45 If a similar situation occurs in Pt-vWD, perhaps the mouse spleen is compensating for a defect in the bone marrow.…”
Section: Discussionmentioning
confidence: 99%
“…12 Macrothrombocytopenia has not been reported in patients or mice deficient in three known GPIb-V-IX ligands, von Willebrand factor, P-selectin and integrin αMβ2, which would argue against the involvement of the extracellular binding domain. 13,14 On the other hand, impaired megakaryopoiesis has been observed in a thrombocytopenic patient with a mutation in the GPIbα interacting site of von Willebrand factor, 15 while decreased megakaryocyte differentiation has been observed in CD34 + cells cultured in the presence of antibodies against the extracellular portion of GPIbα. 16 The intracellular properties of the receptor have also been incriminated in defective platelet biogenesis in relation to the linkage of GPIb-V-IX to the submembranous actin cytoskeleton, which is mediated by filamin.…”
Section: Introductionmentioning
confidence: 99%